2019
DOI: 10.1016/j.jngse.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of methane transport in confined organic nanopores with high relative roughness

Abstract: Understanding and characterizing the transport of shale gas (methane) through the nanopores of kerogens are critical for the accurate prediction of shale gas recovery. However, the key factors that regulate shale gas transport through highly roughened nanopores of shale kerogens are not fully understood. In this work, methane transport in organic nanopores with a high relative roughness is characterized using equilibrium and nonequilibrium molecular dynamics methods. According to our results, the CH 4 mass flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…In the center region, the methane density is uniform (He et al 2019;Yu et al 2020) and the same (within 0.8%) in smooth and rough pores. The density peaks at the substrate indicate the formation of an adsorbed layer of methane.…”
Section: Single-phase Methane Flow In Nanoporementioning
confidence: 86%
See 3 more Smart Citations
“…In the center region, the methane density is uniform (He et al 2019;Yu et al 2020) and the same (within 0.8%) in smooth and rough pores. The density peaks at the substrate indicate the formation of an adsorbed layer of methane.…”
Section: Single-phase Methane Flow In Nanoporementioning
confidence: 86%
“…Previous MD-based research includes nanoscopic simulations of fluid flow, droplet wetting and droplet interactions with smooth and rough solid surfaces. The effect of roughness on the behavior of water nanodroplets (Yaghoubi and Foroutan 2018), wetting transition (Khan and Singh 2014;Koishi et al 2009) and gas flow characteristics (He et al 2019;Yu et al 2020) have been reported. Fang et al (2019) performed MD simulation to elaborate on the mechanisms of extracting hydrocarbon using CO 2 in a nanoscale groove constructed by silicon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While shale nanopores are both rough and irregular, smooth graphite slit pore models have been widely used as a simplified corollary for kerogen nanopores in shale [70][71][72] . Surface roughness affects both the flow dynamics and the adsorption capacity of methane in pores [73][74][75][76] . However, given that our primary goal is to qualitatively compare retention in our model with neutron scattering observations, it warrants the use of smooth surface.…”
Section: Methodsmentioning
confidence: 99%